Application of Ethanol Extracts From Alnus sibirica Fisch. ex Turcz in Hair Growth Promotion - Ha, Eun Ju; Yun, Jang-Hyuk; Si, Chuanling; Bae, Young Soo; Jeong, Young-Hwan; Park, Kwang-Hyun; Choi, Sun-Eun (Frontiers in Bioengineering and Biotechnology, 2021)
Alnus sibirica Fisch. ex Turcz (ASFT), a kind of biomass belonging to the family of Betulaceae, grows naturally in Asia, Europe and America. Generally, there are various constituents in ASFT than can be applied in different bio-fields. In this work, the extract of diarylheptanoid in ASFT branch was isolated and purified using 60% ethanol to determine its preventing effects of hair loss. We investigated anti-oxidative, anti-apoptotic effects on hydrogen peroxide-induced cytotoxicity on human hair dermal papilla cells using MTT assay and Western blotting, respectively. Moreover, we examined ameliorative effects of the extracts of ASFT and oregonin against changes of oxidative stress-induced cytokine and testosterone-induced dihydrotestosterone (DHT) production as crucial pathway on hair loss mechanism. These results suggest that the 60% alcohol extract of ASFT were available candidate for novel natural biomass on maintaining hair health of mammals.